(untitled) (Perner’s Contacts, 2007)
Effective system of electronic fee collection contains enforcement, too. It is a final part of the entire system without which this system could not function rightly and effectively. The article deals with offences. In general how can be the offence recognized, the vehicle and driver identified and the process of penalty recovery. The final part contains offences including electronic fee collection in Slovak republic and experience in foreign countries.